Report of a Novel Homozygous Intragenic DCC Duplication and a Review of Literature of Developmental Split-Brain Syndrome aka Horizontal Gaze Palsy with Progressive Scoliosis-2 with Impaired Intellectual Development Syndrome - Rahikkala Elisa; Väisänen Taneli; Ojala Liisa; Pohjola Pia; Toivonen Minna; Parkkola Riitta; Haanpää Maria K. (Karger Publishers, 2025)
Introduction: Horizontal gaze palsy with progressive scoliosis-2 (HGPPS2, MIM 617542) with impaired intellectual development aka developmental split-brain syndrome is an ultra-rare congenital disorder caused by pathogenic biallelic variants in the deleted in colorectal cancer (DCC) gene.
Case Presentation: We report the clinical and genetic characterization of a Syrian patient with a HGPPS2 phenotype and review the previously published cases of HGPPS2. The genetic screening was performed using exome sequencing on Illumina platform. Genetic analysis revealed a novel DCC c.(?_1912)_(2359_?)dup, p.(Ser788Tyrfs*4) variant segregating recessively in the family. This type of variant has not been described previously in the HGPPS2 patients. To date, including the case reported here, three different homozygous pathogenic frameshift variants, one homozygous missense variant, and an intragenic duplication in the DCC gene have been reported in 8 patients with the HGPPS2 syndrome.
Conclusion: The analysis of duplications and deletions in the DCC should be included in the routine genetic diagnostic evaluation of patients with suspected HGPPS2. This report expands the knowledge of phenotypic and genotypic spectrum of pathogenic variants causing HGPPS2.
Journal Section: Novel Insights from Clinical Practice
Keywords: HGPPS2, DCC, Horizontal gaze palsy, Progressive scoliosis, Intellectual disability, Agenesis of corpus callosum, Duplication